Using the St Andrew's – Swansea Neurobehavioural Outcome Scale (SASNOS) to determine prevalence and predictors of neurobehavioural disability amongst survivors with traumatic brain injury in the community. Issue 9 (21st October 2022) - Alderman, Nick; Williams, Claire; Wood, Rodger Llewellyn
ABSTRACT: Studies using the St Andrew's – Swansea Neurobehavioural Outcome Scale (SASNOS) confirm neurobehavioural disability (NBD) is highly prevalent in inpatient Neurobehavioural Rehabilitation and Stroke samples. However, a recent study amongst a Danish community sample of acquired brain injury survivors found a relative paucity of NBD symptoms; and when symptoms were present, they tended to be of mild severity. The current observational study employed the SASNOS to explore prevalence of NBD in survivors with traumatic brain injury (TBI) living in the community, the extent of survivors' self-awareness of NBD symptoms, and constructed prediction models of NBD. A de-identified data set was compiled, comprising data for 97 TBI survivors (74.2% men, mean time since injury 2.8 years). In addition to SASNOS self- and proxy-ratings, various demographic, clinical and injury-related characteristics were captured. NBD was found to be highly characteristic, although severity varied depending on subtype. Statistical comparison of self- and proxy-ratings did not support reduced self awareness regarding NBD, whereas treating the problem as one of inter-rater reliability suggested this was an issue. Executive impairment, depressed mood and sex were especially prognostic of NBD. Reasons accounting for differences in NBD between the community samples are discussed and recommendations for future research made.